2020
DOI: 10.5093/jwop2020a18
|View full text |Cite
|
Sign up to set email alerts
|

Developing Mindful Organizing in Teams: A Participation Climate is not Enough, Teams Need to Feel Safe to Challenge their Leaders

Abstract: Mindful organizing (also known as collective mindfulness) is a collective capability that allows teams to anticipate and swiftly recover from unexpected events. This collective capability is especially relevant in high-risk environments where reliability in performance is of utmost importance. In this paper, we build on current mindful organizing theory by showing how two front-line communication and participatory conditions (perceived safety for upward dissent and climate for employee engagement) interact to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…The study findings further supported that mindful organizing has a direct effect on both safety compliance and safety participation, and the mediating role of mindful organizing between agility and safety participation has also been supported. The direct effect of mindful organizing is consistent with the prior literature [ 13 , 16 , 17 ], which provides further efficacy to the predictability of mindful organizing for safety performance. Here, it is worthwhile to mention that the number of hazards that prevail in different forms for healthcare workers at their workplace is enormous, e.g., chemical, biological, radiological, and physical.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The study findings further supported that mindful organizing has a direct effect on both safety compliance and safety participation, and the mediating role of mindful organizing between agility and safety participation has also been supported. The direct effect of mindful organizing is consistent with the prior literature [ 13 , 16 , 17 ], which provides further efficacy to the predictability of mindful organizing for safety performance. Here, it is worthwhile to mention that the number of hazards that prevail in different forms for healthcare workers at their workplace is enormous, e.g., chemical, biological, radiological, and physical.…”
Section: Discussionsupporting
confidence: 87%
“…In the literature, studies have testified high-reliability organizations' (HROs) principles, i.e., mindful organizing in healthcare settings previously, and were associated with decreased medication errors, patient falls [8][9][10], and fewer accidents [11]. On the other hand, much of the qualitative evidence is available, which creates a scarcity of quantitative evidence for mindful organizing [12], its antecedents, and its outcomes [13]. Mindful organizing is the collective ability of the workforce to detect anomalies and act swiftly [14].…”
Section: Introductionmentioning
confidence: 99%
“…Reference to the psychometric properties (the internal structure) of the mindful organizing scale, our findings are in harmony with the recent empirical evidence of mindful organizing researches in the context of occupational safety. For instance, standardized factor loadings for mindful organizing in different studies were reported as; ranged from 0.79 to 0.91 with the reliability of .95, [31] from 0.89 to 0.96 with the reliability of 0.94, [15] highly significant factor loading at (P < 0.001) with the reliability of 0.88. [16] Whereas, some of the studies have only reported the healthcare workers at their workplace is crucial for them, but also for the patients they are caring for.…”
Section: Discussionmentioning
confidence: 99%
“…According to many authors [ 46 ], there is a lack of empirical research concerning the collective mindfulness, the most available literature provides qualitative evidence [ 46 ]. There are some exceptions, for example concerning the individual and collective mindfulness in preventing nurses’ work around safety regulations [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigated mindfulness and affective commitment within the health care context, discovering a negative relation with burnout [ 48 ]. Renecle et al [ 46 ] detected a positive impact of collective mindfulness on job satisfaction and, as a consequence, a lower level of turnover intentions.…”
Section: Introductionmentioning
confidence: 99%